PRELIMINARY PHYTOCHEMICAL SCREENING AND HEAVY METAL ANALYSIS OF LEAF EXTRACTS OF ZIZIPHUS OENOPLIA (L) MILL. GARD (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The present study was aimed to investigate the preliminary phytochemical screening of the leaves of Ziziphus oenoplia belonging to family Rhamnaceae. The dried leaves of the plant were subjected to successive Soxhlet extraction by continuous hot percolation method using organic solvents of increasing polarity such as petroleum ether, ethyl acetate and ethanol. The aqueous extract was prepared by cold maceration technique. All the extracts were subjected to qualitative phytochemical screening and it showed the presence of active constituents such as alkaloid, flavonoid, phenol and triterpenoid. Quantitative determination of alkaloid was done by Harborne (1973) method, whereas total Phenolic content was determined by Folin-ciocalteu method and total Flavonoid were determined by the aluminium chloride colorimetric method. Heavy metals and inorganic elements are determined by inductively coupled plasma optical emission spectrometry technique. The results obtained shows that the extracts contain medicinally important bioactive constituents and also heavy metals present in the plant extracts were within the permissible limits. This justifies its use in the traditional medicine for the treatment of different diseases such as ulcer, asthma, dysentery and fever.